Advancing veterinary vaccines design through trained immunity insights - Wang, Xin; Yu, Guohua (Frontiers in Veterinary Science, 2025)
Trained immunity, characterized by long-term functional reprogramming of innate immune cells, offers promising new directions for veterinary vaccine development. This perspective examines how trained immunity can be integrated into veterinary vaccine design through metabolic reprogramming and epigenetic modifications. We analyze key molecular mechanisms, including the shift to aerobic glycolysis and sustained epigenetic changes, that enable enhanced immune responses. Strategic approaches for vaccine optimization are proposed, focusing on selecting effective trained immunity inducers, developing innovative adjuvant systems, and achieving synergistic enhancement of immune responses. While implementation challenges exist, including individual response variations and safety considerations, trained immunity-based vaccines show potential for providing broader protection against emerging pathogens. This approach could revolutionize veterinary vaccinology by offering enhanced efficacy and cross-protection against heterologous infections, particularly valuable for zoonotic disease control.